Trajectory of Rural Education for the social and political conception of Countryside Education in Brazil (Research, Society and Development, 2021)
The following discussions are related to a research linked to the Doctorate in Education of the Graduate Program in Education at the Federal University of Santa Maria. These paper aims to understand the historical context of Rural Education and its relationship with Countryside Education in Brazil in the context of educational public policies. The methogology is characterized as a qualitative approach, based on guiding documents that support the historical context of Rural and Countryside Education and by the following authors: Simões and Torres (2011), Libâneo (2012), Pires (2012), Rossato and Praxedes (2015), Santos (2018), among others. The methodology consists of a bibliographic review aimed at obtaining systematized information about the ways in which Rural and Countryside Education were imprinted in the history of Brazilian education. Reflecting on the issues that led to concepts change is important to understand social and political transformations, which composes an emerging context that still requires knowledge and understanding of legislation on the part of educators/managers. It is necessary to reflect deeply, collectively and methodologically about public policies and governmental actions in order to guarantee a qualified education directed to the reality of the countryside people in Brazil.